The Romance of Leadership and The Evaluation of Organizational Performance - Meindl, James R.; Ehrlich, Sanford B. (Academy of Management Journal, 1987)
Suggesting that as an explanatory concept, leadership has assumed a heroic, larger-than-life quality, this research investigated the effects of leadership attributions on evaluations of organizational performance. In study 1, we found that subjects gave better evaluations to performance outcomes attributed to leadership factors than they gave to the same outcomes when these were attributed to nonleadership factors. Study 2 sought specific information on the nature and quality of leadership's value as an explanatory concept for performance outcomes through analyzing the attributions themselves. The discussion focuses on the phenomenological value and significance of leadership for the analysis of organizations.